2008
DOI: 10.1002/cbic.200800105
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Guanine by Carbonate Radicals Derived from Photolysis of Carbonatotetramminecobalt(III) Complexes and the pH Dependence of Intrastrand DNA Cross‐Links Mediated by Guanine Radical Reactions

Abstract: The carbonate radical anion CO3•− is a decomposition product of nitrosoperoxycarbonate derived from the combination of carbon dioxide and peroxynitrite, an important biological byproduct of the inflammatory response. The selective oxidation of guanine in DNA by CO3•− radicals is known to yield spiroiminodihydantoin (Sp), guanidinohydantoin (Gh), and a novel intrastrand cross-linked product, 5’-d(CCATCG*CT*ACC) between guanine C8 (G*) and thymine N3 (T*) atoms in the oligonucleotide (Crean et al., Nucleic Acids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
77
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(81 citation statements)
references
References 56 publications
4
77
0
Order By: Relevance
“…5) are consistent with the higher proportion of Fpg-sensitive lesions associated with riboflavin compared with ␥-radiation (68). The major lesions observed to date with riboflavin consist of Fpg-sensitive 8-oxo-G and piperidine-sensitive Ox (39, 40, 68 -70), along with smaller amounts of spiroiminodihydantoin, which is sensitive to Fpg (46,71) and partially labile in piperidine (47). The major stable G oxidation products in hydroxyl radical-induced DNA damage (7,72,73) include 8-oxo-G and Ox, along with Fapy-G, which is sensitive to both Fpg and piperidine (40).…”
Section: Discussionmentioning
confidence: 99%
“…5) are consistent with the higher proportion of Fpg-sensitive lesions associated with riboflavin compared with ␥-radiation (68). The major lesions observed to date with riboflavin consist of Fpg-sensitive 8-oxo-G and piperidine-sensitive Ox (39, 40, 68 -70), along with smaller amounts of spiroiminodihydantoin, which is sensitive to Fpg (46,71) and partially labile in piperidine (47). The major stable G oxidation products in hydroxyl radical-induced DNA damage (7,72,73) include 8-oxo-G and Ox, along with Fapy-G, which is sensitive to both Fpg and piperidine (40).…”
Section: Discussionmentioning
confidence: 99%
“…4). In contrast, denaturing gel electrophoresis showed that the standard hot piperidine treatment cleaves 5Ј-CCA-TCG*CT*ACC at G* and T* sites with the release of 5Ј-CCATCp and 5Ј-pACC fragments according to MALDI-TOF/MS analysis (27). This is clear evidence that hot alkali is unable to hydrolyze the G*[C8-N3]T* bond to form the intact T that is generated by the bifunctional DNA glycosylases and AP endonucleases (Figs.…”
Section: Discussionmentioning
confidence: 96%
“…3 and 4). The G*[C8-N3]T* bond is also resistant to nuclease P1, which generates cross-linked dinucleotide d(G*-T*) and d(G*pT*) fragments after complete hydrolysis of the single-stranded DNA containing G*CT* and G*T* IntraCL, respectively (10,27). The phosphodiesterases 1 and 2 do not cleave the phosphodiester bonds between the crosslinked nucleotides (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations